Dampak Perilaku terhadap Intensitas Penggunaan E-wallet dengan Risiko yang Dirasakan Sebagai Variabel Intervening survei pada Gen-Z - Elly Setyawati; Aris Eddy Sarwono (Pusat Riset dan Inovasi Nasional, 2026)
E-wallet usage is growing with the rise of digital payment systems, especially among Generation Z, who are familiar with financial technology. This study analyzes the relationship between usage behavior and e-wallet usage intensity, considering perceived risk as a mediating variable. A quantitative approach was used through a survey of Generation Z respondents who have used e-wallets, with data analysis using the PLS-SEM method via SmartPLS. The test results indicate that usage behavior significantly increases e- wallet usage intensity. Behavior is also positively related to perceived risk, while perceived risk decreases usage intensity. Furthermore, perceived risk is shown to partially mediate the relationship between behavior and usage intensity in a negative direction. These findings confirm that although Generation Z has a high tendency to adopt technology, perceived risk remains a factor influencing consistent e-wallet usage.